Teori Belajar Dan Pembelajaran Dalam Metode Kognitif Di Sekolah - Nurasiah Febrianti; Rahmad idris hasibuan (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to discuss the application of cognitive learning theory in the learning process in elementary schools. The main focus is on how cognitive approaches can improve students' understanding and skills. The research methods used were literature studies and field observations in several elementary schools. Cognitive learning theory was developed by experts such as Jean Piaget and Jerome Bruner, who emphasized the importance of internal mental processes in understanding information. Piaget described four stages of children's cognitive development, while Bruner emphasized discovery-based learning. The research results show that a cognitive approach to learning can increase learning effectiveness, student motivation, as well as critical and creative thinking abilities. Students taught using cognitive methods show active participation in class activities, increased understanding of the material, and higher academic scores compared to traditional learning methods. Teachers report that this method helps students develop higher-order thinking and problem-solving skills. The practical implications of this research suggest that cognitive learning methods should be widely applied in elementary schools to optimize students' learning potential.